Strategi Pengembangan Ekonomi Digital Berkelanjutan di Pekanbaru: Integrasi Teknologi, UMKM, dan Inklusi Keuangan - Maswir, Mulyadi (Eko dan Bisnis: Riau Economic and Business Review, 2025)
The transformation of the digital economy has become a driving force for regional economic growth in Indonesia, including in Pekanbaru, the economic center of Riau Province. This study aims to explain, analyze, and develop a strategic model for sustainable digital economic development based on technology integration, MSME empowerment, and financial inclusion. A mixed-methods approach was employed, combining surveys of 250 MSMEs with in-depth interviews involving 15 key informants from local government, financial institutions, and business associations. Quantitative data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS), while qualitative data were analyzed thematically. The findings show that digital technology integration has a significant positive effect on business efficiency, market expansion, and MSME adaptability. Financial inclusion particularly digital financing access and financial literacy acts as a mediating variable that strengthens the relationship between technological adoption and sustainable digital economy development. Additionally, local government policy support and public-private partnerships enhance the inclusivity of the digital economy ecosystem. The conceptual model developed illustrates the synergistic relationship between technology, MSME capacity, and financial inclusion in achieving digital economic sustainability.